PENGEMBANGAN MEDIA DADU PAPAN PANCASILA BERBASIS GAME BASED LEARNING DI KELAS IV SD/MI - Nazmi, Syafira; M. Daud, Ridhwan; Al Juhra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a Pancasila Board Dice learning media based on Game Based Learning for fourth-grade elementary school students. The background of this research was the limited use of innovative learning media in Pancasila Education, which caused students to become less active and easily bored during the learning process. This study employed the Research and Development (R&D) method using the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included media experts, material experts, language experts, fourth-grade teachers, and 28 fourth-grade students. Data were collected through observation, interviews, validation questionnaires, and response questionnaires. The results indicated that the Pancasila Board Dice media obtained validation scores of 97% from media experts, 82% from material experts, and 85% from language experts, with an overall average score of 88%, categorized as “Very Feasible.” In addition, the practicality test obtained scores of 83% from students and 92% from teachers, with an overall average score of 87%, categorized as “Very Practical.” Therefore, the Game Based Learning-based Pancasila Board Dice media is feasible and practical for use in Pancasila Education learning in fourth-grade elementary schools.